KNOWLEDGE, PERCEPTION, AND BURDEN OF FAMILY IN TREATING PATIENTS WITH SCHIZOPHRENIA WHO EXPERIENCE RELAPSE - Suryani Suryani; Eka Wahyu Ningsih; Aan Nuraeni (Belitung Raya Foundation, Indonesia, 2019)
Background: Schizophrenia is a mental disorder with a high incidence and relapse due to a lack of family support. Families do not understand how to treat patients with schizophrenia. There are several factors related to the family’s abilities in treating patients with schizophrenia, there are the level of family’s knowledge, perception, and burden. Objective: This study aimed to describe the knowledge, perception and burden of family in treating patients with schizophrenia who experience a relapse. Methods: The research used descriptive quantitative method. Samples were selected by consecutive sampling technique and obtained 100 respondents. Data were collected by a questionnaire consisting of family knowledge and perception developed by the researcher, and Zarit Burden Interview scale was used to measure the family burden. Data were analyzed using percentages, score T, and the Zarit Burden Interview analysis. Results: Findings showed that 31 respondents (31%) had good knowledge, 42 respondents (42%) had sufficient knowledge, and 27 respondents (27%) had insufficient knowledge. In terms of perception, 66 respondents (66%) had a positive perception and 33% had a negative perception. In addition, 42 respondents (42%) had moderate to heavy burden levels, 23 respondents (23%) had a very heavy level of heavy burden, and 3 respondents (3%) with very heavy levels of burden. Conclusions: Based on the results, it is necessary to increase the frequency of health education for the families. In addition, it is also important to hold a sharing program between families to reduce family burden.